من الدولة والأمن الاجتماعي...بين التصادم والوفاق - وسيلة, قنوفي (University of Eloued جامعة الوادي, 2020)
ي من أبرز التحديات التي تواجه المجتمعات الإنسانية المعاصرة في عالم تتنازعه تيارات إيديولوجية مختلفة،ورغم أن الفهم العام للأمن الاجتماعي يتمثل في كونه مسؤولية الدولة إلا أن الاستقرار الأمني داخل الدولة لا يتأتى إلا بضبط المعادلة بين أمن الدولة وأمن أفرادها، عن طريق الإدارة َ المعقولة لاحتكار حق استخدام القوة والإكراه، في حُ دود متطلبات دولة القانون، فتظل الدولة المسؤول الأول عن أمنها وأمن أفرادها،في إطار احترام حقوق الإنسان وحرياته الأساسية.Community security counts among the major challenges facing contemporary human societies in a world torn apart by different ideological currents. Although the general concept of community security consists in considering it the responsibility of the State, security stability within the State can only be achieved through finding the right balance between the security of the State and that of its citizens, through the reasonable administration of the monopoly of the right to use force and coercion, within the limits of the needs of the rule-of-law, since the State remains solely responsible for its own security and that of its citizens, within the framework of respect for human rights and fundamental freedoms
محلد11، عدد1
Keywords: من الاجتماعي؛ الاستقرار الأمني؛ التماسك الاجتماعي؛ المواطنة؛ الصراعات الاثنية; State security; community security; security stability; social cohesion; citizenship; ethnic conflicts.